R1224yd(Z), R1233zd(E) and R1336mzz(Z) as replacements for R245fa: Experimental performance, interaction with lubricants and environmental impact. (15th April 2021) - Dawo, Fabian; Fleischmann, Jonas; Kaufmann, Florian; Schifflechner, Christopher; Eyerer, Sebastian; Wieland, Christoph; Spliethoff, Hartmut
Highlights: Analysis of R1224yd(Z), R1233zd(E) and R1336mzz(Z) as replacements for R245fa. Experimental Investigation and Modelling of oil/refrigerant mixtures. Life Cycle Assessment of novel low-GWP refrigerants in ORC applications. Abstract: Achieving the 2050 EU climate targets - an economy with net-zero greenhouse gas emissions - requires a significant increase in the share of renewables in the current energy mix. The Organic Rankine Cycle (ORC) could play an important role in this transformation of today's energy systems. The ORC is able to convert low-temperature heat sources into electrical power by utilizing refrigerants as working fluids. Many of these refrigerants have a significant global warming potential (GWP) and recent legislations therefore increasingly limit their use. In recent years a new generation of refrigerants has been developed. These refrigerants are characterized by low global warming potentials and are considered as replacements for the old high-GWP refrigerants. In this paper R1224yd(Z), R1233zd(E) and R1336mzz(Z) are investigated as possible replacements for the state of the art high-GWP refrigerant R245fa. These novel fluids have quite similar thermophysical properties and can thus potentially be used as drop-in replacements for R245fa. For the application as drop-in replacement and the correct interpretation of measurement data, the interaction of the refrigerant with the used lubricant is important. Therefore, the interaction of all four refrigerants with a typical lubricant oil is experimentally investigated first. A novel model based on Raoult's law is introduced and validated with experimental data. The model allows the computation of the liquid and vapor phase composition of refrigerant/oil-mixtures using pressure and temperature measurements. In the next step, the performance of the four investigated refrigerants is evaluated experimentally in an ORC test rig. Therefore, the same experimental program was repeated for every refrigerant in order to ensure a fair comparison. To conclude the evaluation of the refrigerants, a Life Cycle Assessment (LCA) is conducted for a theoretical geothermal power plant operated with the four considered refrigerants. The experimental results show, that R1224yd(Z) as well as R1233zd(E) are very suitable low-GWP alternatives for R245fa and could be used as drop-in replacements. R1336mzz(Z) on the other hand shows significantly lower system efficiencies and power outputs compared to the other refrigerants. The highest power output and system efficiency is however still achieved by the state of the art refrigerant R245fa, but these quantities are only slightly lower for R1233zd(E) and R1224yd(Z) . The LCA based on the experimental results for a hypothetical large-scale geothermal ORC application reveals, that despite the slight performance decrease, the application of low-GWP fluids decreases the CO2 -equivalent of the system significantly. The usage of R1233zd(E) could decrease the CO2 -equivalent by 67% compared to R245fa.